Physical Fitness Level of Students at Tiga Hati Kepenuhan Hulu Middle School (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to survey and analyze the physical fitness levels of students at SMP Tiga Hati Kepenuhan Hulu. Physical fitness is a fundamental aspect of health and adolescent development. The research population consisted of all students at SMP Tiga Hati Kepenuhan Hulu, totaling 167 individuals, from which a sample of 65 respondents was selected using the Slovin formula. Data were collected using the Indonesian Physical Fitness Test (TKJI) for ages 13–15, which includes speed (50-meter run), arm muscle strength (pull-up/hanging arm bent), abdominal muscle endurance (sit-up), leg muscle explosive power (vertical jump), cardiorespiratory endurance (1000/800-meter run), and flexibility (sit and reach). Test results were converted into scores and classified using the TKJI criterion-referenced assessment (PAP). The results showed that, in general, the physical fitness level of students at SMP Tiga Hati Kepenuhan Hulu fell into the “Moderate” category (45%) and “Poor” category (35%), with only 18% in the “Good” category and none achieving the “Very Good” category. Specifically, the components of leg explosive power (Vertical Jump) and cardiorespiratory endurance (Distance Run) showed very low levels, with all students (100%) categorized as “Poor” or “Very Poor” for leg explosive power, and the majority (98%) in the “Very Poor” category for cardiorespiratory endurance. The components of speed, arm muscle strength, abdominal muscle endurance, and flexibility also indicated that most students were in the lower-middle performance categories. These findings highlight an urgent need for a well-planned and sustainable physical fitness improvement program at SMP Tiga Hati Kepenuhan Hulu